Mental Causation - Kroedel, Thomas (Cambridge University Press, 2022)
This book presents a comprehensive account of how the mind causes things to happen in the physical world. It will be of interest to a range of readers in philosophy of mind, metaphysics, and philosophy of science. This book is also available as Open Access.